2017
DOI: 10.1080/09553002.2017.1325971
|View full text |Cite
|
Sign up to set email alerts
|

Increasing levels of saliva alpha amylase in electrohypersensitive (EHS) patients

Abstract: The purpose: The objective of this study was to assess the level of various salivary and urinary markers of patients with EHS and to compare them with those of the healthy control group. Materials and methods:We analyzed samples from 30 EHS individuals and a matched control group of 25 individuals (non EHS) aged between 22 and 66. We quantified cortisol both in saliva and urine, alpha amylase (sAA), immunoglobulin A and C Reactive Protein levels in saliva and neopterin in urine (uNeopterin).Results: sAA was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…This did not show any changes in this physiological parameter [76]. Our present study, in line with other studies [77,78], did not support the hypothesis of a direct cause-effect relationship between RF exposure and dysfunction of the skin for certain parameters.…”
Section: Discussionsupporting
confidence: 75%
“…This did not show any changes in this physiological parameter [76]. Our present study, in line with other studies [77,78], did not support the hypothesis of a direct cause-effect relationship between RF exposure and dysfunction of the skin for certain parameters.…”
Section: Discussionsupporting
confidence: 75%
“…In a study by Nag & Pradhan ( 100 ) in a sample of 2105 community population, it was revealed that although higher sCRP levels were observed among evening types, but morningness/eveningness didn’t have any significant relationship with sCRP levels. Moreover, Andrianome et al ( 101 ) showed that in a sample of 30 electro-hypersensitive individuals and 25 matched control groups aged between 22 and 66, sCRP levels significantly increased in the morning for both groups. Harnett et al ( 96 ) found that there are associations between decreased sleep quality and sleep quantity with increased sCRP levels among a sample of 19 rugby player athletes.…”
Section: Resultsmentioning
confidence: 99%
“…Andrianome et al ( 101 ), in a sample of 55 adults aged between 22 and 66, showed that sCRP level was negatively correlated with age. Moreover, Jones et al ( 125 ) in a sample of 151 community children and adults, didn’t find any associations between sCRP level with age.…”
Section: Resultsmentioning
confidence: 99%
“…Over a dozen studies have focused on symptoms reported by self‐declared electro‐hypersensitive (EHS) persons, consistently demonstrating that these symptoms are subjective, non‐specific, and widespread in the healthy population—as is the case for all medically unexplained symptoms [Creed et al, ]. Furthermore, no specific biomarker of IEI‐EMF has been identified [De Luca et al, ; Belpomme et al, ; Andrianome et al, ]. It is therefore impossible, based on these results, to characterize IEI‐EMF or to distinguish it from other functional somatic syndromes [Barsky and Borus, ] and somatoform disorders.…”
Section: Introductionmentioning
confidence: 99%